A facile approach to tryptophan derivatives for the total synthesis of argyrin analogues - Chen, Chou-Hsiung; Genapathy, Sivaneswary; Fischer, Peter M.; Chan, Weng C. (Royal Society of Chemistry, 2014)
A facile route has been established for the synthesis of indole-substituted (S)-tryptophans from corresponding indoles, which utilizes a chiral auxiliary-facilitated Strecker amino acid synthesis strategy. The chiral auxiliary reagents evaluated were (S)-methylbenzylamine and related derivatives. To illustrate the robustness of the method, eight optically pure (S)-tryptophan analogues were synthesized, which were subsequently used for the convergent synthesis of a potent antibacterial agent, argyrin A and its analogues.